Hi I am trying to teach myself maths. So go easy on me if these are stupid questions.

I have the equations
$x^2 - x - 6$

I need to find out the values of A,B,C so I can plug them into the quadratic equation to find the roots.

The example in the book says

Ok so for Example 1. where x^2 - x - 6
What are a, b, and c so we can plug them into the quadratic equation to find x?

(1)x^2 - (1)x - 6 = 0

Let's get it into the exact form of [ax^2 + bx +c = 0]

(1)x^2 + (-1)x + (- 6) = 0
a b c

therefore...
a = 1
b = -1
c = -6
But I do not understand this,... dose this mean that the a,b,c for

$x^2-2x+1$
a= 1
b= -2
c= 1

$x^2+2x+5$
a = 1
b = 2
c = +1

???

Is that correct?

2. Originally Posted by anewhobby
Hi I am trying to teach myself maths. So go easy on me if these are stupid questions.

I have the equations
$x^2 - x - 6$

I need to find out the values of A,B,C so I can plug them into the quadratic equation to find the roots.

The example in the book says

But I do not understand this,... dose this mean that the a,b,c for

$x^2-2x+1$
a= 1
b= -2
c= 1

$x^2+2x+5$
a = 1
b = 2
c = +1

???

Is that correct?
yes that is correct and then you can use it in the formula.